Overview of the Epizootiological Situation on Highly Pathogenic Avian Influenza Virus in Russia in 2019 - V. Yu. Marchenko; N. I. Goncharova; Thi Nhai Tran; Khac Sau Trinh; Ngoc Quyen Nguyen; E. V. Gavrilova; R. A. Maksyutov; A. B. Ryzhikov (Problems of Particularly Dangerous Infections, 2020)
This review describes the current situation on highly pathogenic avian influenza virus in 2019 and predicts the possible further spread of avian influenza in Russia. In 2019 outbreaks were reported among wild birds and poultry, as well as human infections with influenza viruses of the subtypes H5Nx, H7N9 and H9N2 in several countries. In 2019, only two outbreaks of highly pathogenic avian influenza H5N8 in Russia occurred. Both outbreaks were recorded in January at poultry farm in the Rostov Region. In addition, in May 2019 avian influenza virus of H14N7 subtype was isolated from a wild bird during the avian influenza virus surveillance in Tomsk Region. In June 2019, a strain of H13N2 subtype was isolated in the territory of Kamchatka Region, then, in August 2019, an influenza virus of H13N6 subtype was isolated in the Saratov Region. It was revealed that some strains of avian influenza virus isolated in Russia have a high degree of identity with strains circulating in South-East Asia. This was shown by the phylogenetic analysis of A/ H5Nx influenza viruses previously isolated in the Saratov Region and the Socialist Republic of Vietnam during the avian influenza virus surveillance. Thus, it was demonstrated again that the territory of Russia plays a key geographical role in the global spread of avian influenza virus.